(3QjGV GdCfS GdYbdGA GdEfS aj eYQaI CUd CMhGd GdfHi Udi Gddg Ydjg hSde efP hdO Edi Cf dMO hJGQjN GdNdaGA HYOgs - (3TjQhjg (B((3TjQhjI(B) (3Hf TgQOGQ Hf TjQh jg Hf afGNSQh, CHh TLGY GdOjdeqj GdgePGfj,J (B509 (3g` s ((3CHh eMeO YHO Gddg Hf YHO Gdedc Hf CHj GdMSf s)
(3ChdgG (B:s
(3CeG HYO , aEfi LeYJ dc cJGHkG eajOkG CPcQ ajg SjQI GdfHi Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hRjQg eMeO Hf eMeO Hf eMeO Hf LgjQ , hGddg (B[ (3CYde (B] (3HeG jchf HYO Pdc hge KeGfjI hYTQhf Je GdcJGH s
(3JedcgG GdfGSNs
(3YdjgG SeGYGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B183 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B313s
Keywords: (3GdJGQjNs